Arte e engajamento na filosofia sartreana - Martins, Gabrielle Fernandes (2022)
The present work has as main objective to examine a specific cut about what Sartre proposed about art: the relationship between art and engagement. Sartre writes What is literature? (1949) to explain his understanding of literature and how engagement is present in this art. However, still the association with a strictly political engagement or some confusion about what this engagement is remained happening. Thus, the effort here is, to understand what Sartre argues is art, and on the other hand, to understand what the senses of engagement present in the thought of this philosopher are. For this, firstly, we follow the explanation of how Sartre understands art and its relationship with what he calls imagining consciousness. Second, the understanding of what Sartre means by engagement. And, finally, the elucidation of literature as the work of art that, according to the philosopher, is likely to be engaged, highlighting literature as an appeal to the freedom of the other.